ANALISIS MARGIN PEMASARAN WORTEL DI DESA SINISIR KECAMATAN MODOINDING - Finka Erika Dongi; Noortje M. Benu; Gracet Adonia Josefina Rumagit (AGRI-SOSIOEKONOMI, 2019)
This study aims to determine marketing patterns, calculate the amount of margins, profit and marketing costs as well as farmer's share in Sinisir Village, Modoinding Sub-district, Minahasa Regency. This research was conducted from June to August 2018. The data used in this study are primary and secondary data. Primary data were collected from interviews based on a list of questions prepared previously on 14 respondents consisting of 10 farmers from Sinisir Village, 1 collecting trader from Tompaso Baru Dua Village, 2 retailers from Tompaso Baru Dua Village and in Karombasan Village, 1 big trader from Sinisir Village, Modoinding District. Whereas secondary data was obtained from the Sinisir Village Office of Modoinding District from local bookstores and from the internet. From the internet through google searching in the form of books and theses from other universities. The results showed that there were four forms of marketing channels in Sinisir Village, Modoinding District, namely: (I) Farmers - Consumers; (II) Farmers - Retailers - Consumers; (III) Farmers - Collector Traders - Retailers Traders - Consumers; IV) Farmers - Wholesalers. The carrot marketing channel which produced the highest cost, margin and marketing profit in marketing channel II was Rp 5,429 per kilogram, Rp 6,000 per kilogram, Rp 571 per kilogram. The highest farmer's share in marketing channel 1 is 100 percent.*eprm*